Kebijakan Telemudik Bentuk Perlindungan Negara Pada Masyarakat Menuju New Normal Ditengah Pendemi Corona - Amalia Syauket; Bambang Karsono; Dwi Atmoko (Jurnal Kajian Ilmiah, 2022)
The number of people who have died from COVID-19 has also continued to increase, as has the number of people infected with the Corona virus (Covid-19). Until May 2021, which coincides with the Eid al-Fitr 1442 H, which is the custom of the people of Jakarta, to go home to stay in touch with family in the area. At that time, Jakarta was still in the red zone due to the spike in the spread of Covid-19 cases. The state, in this case the Government, must be present to protect its people, both those infected with COVID-19 and so that they are not infected with Covid-19. This protection is in the form of the issuance of a regulation in the form of a Covid-19 Handling Task Force Circular Number 13 of 2021 concerning the Elimination of Homecoming for Eid Al-Fitri in 1442 Hijri and efforts to control the spread of Covid-19 during the holy month of Ramadan 1442 Hijri to change the ignorance of the people towards the Covid-19 pandemic. This study uses a qualitative approach by prioritizing secondary data, to find out the background of the issuance of the telemudik policy. The conclusion drawn from this literature research is that the background behind the birth of the telemudik policy is the ignorance of the community towards the covid pandemic itself. The right solution for carrying out homecoming during the Covid-19 pandemic is telemudik not to reduce the essence of friendship and sharing and prepare the community for the New Normal. in the midst of the Corona pandemic.